IL-2 imprints human naive B cell fate towards plasma cell through ERK/ELK1-mediated BACH2 repression. Issue 1 (December 2017) - Hipp, Nicolas; Symington, Hannah; Pastoret, Cédric; Caron, Gersende; Monvoisin, Céline; Tarte, Karin; Fest, Thierry; Delaloy, Céline
Abstract Plasma cell differentiation is a tightly regulated process that requires appropriate T cell helps to reach the induction threshold. To further understand mechanisms by which T cell inputs regulate B cell fate decision, we investigate the minimal IL-2 stimulation for triggering human plasma cell differentiation in vitro. Here we show that the timed repression of BACH2 through IL-2-mediated ERK/ELK1 signalling pathway directs plasma cell lineage commitment. Enforced BACH2 repression in activated B cells unlocks the plasma cell transcriptional program and induces their differentiation into immunoglobulin M-secreting cells. RNA-seq and ChIP-seq results further identify BACH2 target genes involved in this process. An active regulatory region within theBACH2 super-enhancer, under ELK1 control and differentially regulated upon B-cell activation and cellular divisions, helps integrate IL-2 signal. Our study thus provides insights into the temporal regulation of BACH2 and its targets for controlling the differentiation of human naive B cells. T cells help B cells to differentiate into antibody-producing plasma cells. Here the authors show that T cells produce interleukin-2 to activate ERK/ELK1 and suppress BACH2 expression by modulating the BACH2 super-enhancer, thereby altering BACH2 downstream transcription programs for plasma cell differentiation.